Rational Design, Synthesis and Evaluation of Coumarin Derivatives as Protein‐protein Interaction Inhibitors. Issue 8 (25th July 2016) - De Luca, Laura; Agharbaoui, Fatima E.; Gitto, Rosaria; Buemi, Maria Rosa; Christ, Frauke; Debyser, Zeger; Ferro, Stefania
Abstract: Herein we describe the design and synthesis of a new series of coumarin derivatives searching for novel HIV‐1 integrase (IN) allosteric inhibitors. All new obtained compounds were tested in order to evaluate their ability to inhibit the interaction between the HIV‐1 IN enzyme and the nuclear protein lens epithelium growth factor LEDGF/p75. A combined approach of docking and molecular dynamic simulations has been applied to clarify the activity of the new compounds. Specifically, the binding free energies by using the method of molecular mechanics‐generalized Born surface area (MM‐GBSA) was calculated, whereas hydrogen bond occupancies were monitored throughout simulations methods. Abstract :